Hedge Accounting: International Financial Reporting Standards and Standards of the Central Bank of Brazil - Iudícibus, Sérgio de (2020)
In 2008 it was announced the revision of International Accounting Standard (IAS 39), segmented into three main stages, the classification and measurement of financial instruments, the introduction of a new methodology for the calculation of impairment and hedge accounting. This project resulted in the publication in July 2014 of the new Standard of Financial Instruments, IFRS 9. The objective of this study was to analyze the main impacts brought by IFRS 9, in comparison with accounting standards in the Accounting Plan of National Financial System Institutions (COSIF), in relation to accounting for hedge accounting. A comparative analysis of local and international regulations was carried out and, in a complementary manner, was analyzed the impact of the application of international accounting standards on Brazilian accounting statements in Generally Accepted Accounting Principles of Banco Société Générale do Brazil, basis of June 30 2017. The results of the research show that, with the changes introduced by IFRS 9, more detailed information on hedge accounting has been required, which considerably impacts the content and the current format of the explanatory notes. The analysis of the financial institution's explanatory notes revealed the need for adequacy as to the way of discloser the items designated as hedge instruments, separately by risk category, and as to the required format, present a level of detail of the values by risk category for types of hedge. In this sense, the study's main contribution is to demonstrate that the local requirements of the disclosures of financial instruments need adjustments.